THE BALANCE OF POWER AND THE CRIMEAN WAR (1853 – 1856) - Dodovska, Ivanka (Institute for Democracy Societas Civilis - Skopje, IDSCS. Konrad Adenauer Stiftung., 2015)
In 1815, the four major European powers met in Vienna with a single purpose: “To ensure the fi nal and irrevocable end of the Napoleonic hegemony!” Their mission was far from simple; however, they were strongly driven by the need to restore the pride of the dynastic heritage which was violently usurped and devalued by the illegitimate French emperor. At that moment, regardless of their family connections, the representatives of England, Austria and Prussia hypocritically accepted the Russian Tsarist autocracy, embodied in the great Russian Tsar Alexander I who, in terms of the decisions that emerged from the Congress of Vienna (like Wilson in 1919), was the main protagonist and was certainly the creator of the informal union called the Holy Alliance. In terms of the foreign policy of Tsarist Russia, this entire creation signifi ed a stable terrain and a guarantee of its foreign policy plans aimed at the Ottoman Empire, as well as further expansion of its infl uence in the region of Southeast Europe, where a substantial Orthodox population lived under Ottoman Sharia rule for several centuries. Given the circumstances, the Russian court was shocked to learn that, after the declaration of war against the Ottoman Empire in 1853, the Russian navy found itself standing against not only the Ottoman, but also the British and French naval forces, an unprecedented event in the autocratic era where, in wartime, Christian countries sided with a Muslim country against another Christian country. Considering the reasons listed above, this paper aims at providing a comparative analysis of the decisions made at the Vienna Congress of 1815 in terms of the changes that conditioned the established balance of power in Europe. Additionally, we intend to compare the Treaty of Küçük Kaynarca of 1774 with the decisions of the Treaty of Paris of 1856, considering them the most adequate indicator of the geopolitical interests that will condition the international system throughout the 20th century.
Keywords: Француска револуција, Виенски конгрес, Света Алијанса, Кримска војна, Париски договор 1856 година.